Understanding the small-world nature of board network in India - Shreya Biswas (Cogent Economics & Finance, 2019)
The study analyzes the small-world nature of the board interlock network for National Stock Exchange-listed firms in India. The small world is the notion that each firm can reach any other firm in the network through a small number of intermediate firms. We find that since the introduction of corporate governance regulations in India, the small worldliness of the network has increased, indicating the concentration of directorial positions in the hands of few elites in the country. The small-world nature of the network can be attributed to the presence of few linchpins in the network and the majority of the linchpins are business group firms in the country. The linchpin acts as a bridge between otherwise sparsely connected clusters in the network. The firms that act as linchpins have higher profitability on account of access to a larger pool of resources.
Keywords: 330; small world; board of directors; inter-firm network; firm performance